Exploring a Safe Zone-Based Locomotion Method with Natural Movement and Adaptive Teleportation for Immersive Environments - Pereira, Lucas Alviene; Negrão, Matheus D.; Maciel, Anderson; Torchelsen, Rafael; Nedel, Luciana; Freitas, Carla M. D. S. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Virtual Reality (VR) offers immersive experiences, but navigating VR environments often faces a significant hurdle: physical space limitations. Virtual worlds commonly exceed the user’s real-world space, restricting natural movement. Traditional locomotion techniques like teleportation and continuous directional movement are widely used as an alternative. This work presents a locomotion approach that aims to improve navigation in virtual environments considerably larger than the available physical space. It leverages the available physical space for increased real movement and uses teleportation for longer distances. To achieve this, we introduce the concept of S-zones, which are pre-defined safe zones that encompass disjoint sets of interactive elements. This approach encourages and allows users to physically move naturally within these S-zones, reserving teleportation for reaching more distant areas. The goal is to minimize the need for teleportation for nearby interactions, making them more natural and reducing the potential for cybersickness or spatial disorientation caused by unnatural body movement, such as joystick locomotion. Herein, we also report an experiment that we conducted with 20 participants, which gave us the first insights regarding our approach and allowed us to foresee the next steps of our research.